TEMPORAL ANALYSIS OF URBANIZATION AND RESULTING LOCAL WEATHER CHANGE: A CASE STUDY OF BAHAWALPUR, PUNJAB, PAKISTAN - Muhammad Zaib Arshad; Muhammad Saeed; Zafar Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines climatic and environmental changes in Bahawalpur, Punjab, Pakistan, from 1992 to 2022. According to key findings, the Mean Annual Temperature has climbed dramatically over the analyzed period, by over 6°C. Both daytime and nightly temperatures have been gradually rising in preparation for hotter days and warmer nights. Rainfall patterns during the last 30 years have displayed cyclical fluctuations rather than a linear trend, causing challenges with water resource management. Different changes in land use patterns have been observed as Bahawalpur’s vegetation increased by 5.54%, urban areas increased by 0.45%, and barren land decreased by 5.99%. This trend indicates an increase in urbanization and green space. The data shows that strategic measures and legislative changes are required to address the environmental difficulties that Bahawalpur is facing.